Innovative Leadership In Building A Dynamic And Creative Marketing Team: A Systematic Literature Review - Yona Kartika Sari; Yunia Wardi; Ilham Thaib (Eduvest - Journal of Universal Studies, 2024)
This journal discusses the trend of innovative leadership in the context of successful marketing strategies, with a focus on building dynamic and creative teams. Innovative leadership is identified as a key factor in facilitating effective collaboration and creativity among marketing team members. A corporate culture that supports innovation is also considered an important cornerstone of a successful marketing strategy. Innovation is understood to be a continuous process, not a one-off event, with innovative leaders ensuring that teams continue to push the boundaries of their creativity and are not satisfied with the status quo. By understanding and applying these principles, companies can build dynamic and creative teams, which is key in meeting the challenges and opportunities in a changing market.